Grenada - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
With some 19 million US Dollars (1.6 percent of GDP) in unresolved arrears to official bilateral creditors, Grenada remains in external public debt distress. However, debt appears sustainable reflecting favorable projected debt dynamics from substantial fiscal surpluses that are supported by the Fiscal Responsibility Law (FRL). Total public debt has declined from 108 percent of GDP in 2013 to 63.5 percent of GDP in 2018, with external public debt amounting to 44.5 percent of GDP. This reduction was made possible through fiscal consolidation that has been anchored by the FRL, robust economic growth, and a restructuring of Grenada's public debt. Going forward, continued adherence to the FRL and regularization of arrears will be needed to upgrade the risk rating. Debt should be further reduced and kept at levels needed to withstand the existing vulnerabilities to external shocks and natural disasters.